Mongrel Nation Diasporic Culture and the Making of Postcolonial Britain - Dawson, Ashley (University of Michigan Press, 2007)
Mongrel Nation surveys the history of the United Kingdom's African, Asian, and Caribbean populations from 1948 to the present, working at the juncture of cultural studies, literary criticism, and postcolonial theory. Ashley Dawson argues that during the past fifty years Asian and black intellectuals from Sam Selvon to Zadie Smith have continually challenged the United Kingdom's exclusionary definitions of citizenship, using innovative forms of cultural expression to reconfigure definitions of belonging in the postcolonial age. By examining popular culture and exploring topics such as the nexus of race and gender, the growth of transnational politics, and the clash between first- and second-generation immigrants, Dawson broadens and enlivens the field of postcolonial studies.